2017
DOI: 10.4103/ijo.ijo_863_16
|View full text |Cite
|
Sign up to set email alerts
|

Insight into high myopia and the macula

Abstract: The incidence of myopia is constantly on the rise. Patients of high myopia and pathological myopia are young and can lose vision due to a number of degenerative changes occurring at the macula. With the emergence of new technologies such as swept-source optical coherence tomography (OCT) and OCT angiography, our understanding of macular pathology in myopia has improved significantly. New conditions such as myopic traction maculopathy have been defined. Early, noninvasive detection of myopic choroidal neovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 79 publications
1
29
0
2
Order By: Relevance
“…Our study showed a significant decrease in the SFCT in myopic eyes ( p < 0.001), in line with the findings of others [2,7,19,[25][26][27]. Choroidal thinning is one of the earliest signs of non-pathological myopic change and can lead to pathological changes later, such as lacquer crack formation and choroidal neovascularization, and is associated with a poorer prognosis [2,3,7,8,9,15]. However, choriocapillaris blood flow results are controversial in the literature.…”
Section: E Fsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study showed a significant decrease in the SFCT in myopic eyes ( p < 0.001), in line with the findings of others [2,7,19,[25][26][27]. Choroidal thinning is one of the earliest signs of non-pathological myopic change and can lead to pathological changes later, such as lacquer crack formation and choroidal neovascularization, and is associated with a poorer prognosis [2,3,7,8,9,15]. However, choriocapillaris blood flow results are controversial in the literature.…”
Section: E Fsupporting
confidence: 84%
“…Myopia is the leading cause of vision impairment, affecting more than 1.4 billion people worldwide [1][2][3][4][5][6][7][8][9][10]. Its prevalence has been increasing in Asia [1][2][3]5,7,[9][10][11][12][13][14]. Myopia with a refractive error >-6 diopters (D) or an axial length >26 mm is considered pathologic.…”
Section: Original Articlementioning
confidence: 99%
“…It can be classified as physiologic and pathologic. The cause of physiological myopia can be high curvature of the cornea, nuclear sclerosis and elongated eyeball or combination of these factors with the absence of any other ocular pathology 3 . The cause of pathologic myopia is abnormal lengthening of the eyeball leading to thinning of the sclera wall and other complications.…”
Section: Introductionmentioning
confidence: 99%
“…Not only it has a social impact on the individual, making the person unable to perform the tasks of desire, it acts as a factor in adding individuals with less productivity 6 . Furthermore, myopia is a risk factor for other visually blinding diseases like glaucoma 3 and retinal detachment 3 which further implicates on the health system. For these reasons the pathophysiology of development of myopia remained a hot debate since ages.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior staphyloma (PS) is sine qua non of pathological myopia. [ 1 ] It is characterized by disproportionate scleral ectasia with stretched conforming retinochoroidal layers. Conventionally, it has been classified into multiple types depending on location, although it usually involves the posterior pole of the eye.…”
mentioning
confidence: 99%